Effects of sodium cationization versus protonation on the conformations and N-glycosidic bond stabilities of sodium cationized Urd and dUrd: solution conformation of [Urd+Na]+ is preserved upon ESI. Issue 27 (30th June 2017) - Zhu, Y.; Roy, H. A.; Cunningham, N. A.; Strobehn, S. F.; Gao, J.; Munshi, M. U.; Berden, G.; Oomens, J.; Rodgers, M. T.
Abstract : The conformations of sodium cationized uridine and 2′-deoxyuridine are sensitive to the presence (or absence) of the 2′-hydroxyl substituent. IRMPD action spectroscopy studies suggest that the solution conformation of [Urd+Na] + is preserved upon ESI. Abstract : Uridine (Urd) is one of the naturally occurring pyrimidine nucleosides of RNA. 2′-Deoxyuridine (dUrd) is a naturally occurring modified form of Urd, but is not one of the canonical DNA nucleosides. In order to understand the effects of sodium cationization on the conformations and energetics of Urd and dUrd, infrared multiple photon dissociation (IRMPD) action spectroscopy experiments and density functional theory (DFT) calculations are performed. By comparing the calculated IR spectra of [Urd+Na] + and [dUrd+Na] + with the measured IRMPD spectra, the stable low-energy conformers populated in the experiments are determined. Anti oriented bidentate O2 and O2′ binding conformers of [Urd+Na] + are the dominant conformers populated in the experiments, whereas syn oriented tridentate O2, O4′, and O5′ binding conformers of [dUrd+Na] + are dominantly populated in the experiments. The 2′-hydroxyl substituent of Urd stabilizes the anti oriented O2 binding conformers of [Urd+Na] + . Significant differences between the measured IRMPD and calculated IR spectra for complexes of [Urd+Na] + and [dUrd+Na] + involving minor tautomeric forms of the nucleobase make it obvious that none are populated in the experiments. Survival yield analyses based on energy-resolved collision-induced dissociation (ER-CID) experiments suggest that the relative stabilities of protonated and sodium cationized Urd and dUrd follow the order: [dUrd+H] + < [Urd+H] + < [dUrd+Na] + < [Urd+Na] + . The 2′-deoxy modification is found to weaken the glycosidic bond of dUrd versus that of Urd for the sodium cationized uridine nucleosides.